Qualidade da água de rios e sistemas de esgotamento sanitário - Pessoa, Jonatan Onis (2016)
Sewage systems when properly operated can help to minimize of aquatic environments degradation. In this context, this study aimed to evaluate the river water quality in towns with and without sewage. Therefore, ten towns of Bahia State were selected, seven of them containing sewage and three devoid of such services. It was used secondary data from water river quality (INEMA – Environmental Stare Agency), sewage (SNIS). Parameters analyzed were concentration of fecal coliforms, biochemical oxygen demand, total phosphorus, dissolved oxygen and the Water Quality Index - IQA 14 points monitored in the period 2008 to 2015. Data were submitted the statistical analysis using the Kruskal-Wallis test. It was found that average AQI values ranged from 26 to 72. The four points monitored in towns without public sewage system presented classified waters as "good" while 40% of monitored points in cities with SES have waters classified as "regular 'or' bad '. Results suggest that the release of sewage into storm water systems and receiving bodies seems to be the main cause of low AQI values. Thus, there has been the weakness of the towns as the supervision of illegal sewage connections. Environmental education campaigns are recommended in order to reduce such practices and to improve water quality in rivers in these towns.